The Concept of Fitrah and Its Correlation With The Theory of Knowledge Development in Islamic Education - Andry Fitriyanto (AT-TURATS, 2020)
This article aims to explain the concept of fitrah in the treasures of Islamic thought. This discussion cannot be released in the discourse of Islamic Education. The presence of the perspective of Muslim thinkers on this fitrah issue in order to fill the empty space created from the discussion about Islamic education. On the other hand, this article also discusses the correlation of the concept of fitrah with the theory of human knowledge development commonly used in the world of education in general, namely the theory of empirics, nativism, and convergence. As we know that the theories born in secular Western civilization is not entirely in accordance with the concept of fitrah which is the original concept of Islam that upholds divine values. The linking of the two variables seems forced in the discourse of Islamic education science so far. Therefore, efforts are needed to present the interpretation of the concept of fitrah and stages of development of human knowledge in the perspective of Islamic thought. This is to show the theory of the development of human knowledge in accordance with islamic teachings. Simply put, this article also wants to convey that human nature has two aspects, namely godliness and humanity. Where both natural potentials must be developed in the context of Islamic education